2021
DOI: 10.1177/2165079921993110
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Occupational Health Professionals Understanding and Needs in Regard to Total Worker Health (TWH)

Abstract: Background: Occupational health professionals (OHPs) are in a unique position to impact the health and well-being of employees at work and outside of work. One way of achieving this holistic health goal is to integrate the concept of Total Worker Health® (TWH) into the organization’s culture. It is critical for OHPs to develop the ability to incorporate TWH into their practices, yet there are gaps in our understanding of OHP’s attitudes toward change and toward TWH, their level of TWH knowledge, and the number… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 9 publications
0
5
0
2
Order By: Relevance
“…Ganzheitliche Ansätze der arbeitsmedizinischen Betreuung wer den auch international diskutiert. In einer USamerikanischen Studie (Olszewski et al 2021) wurde im Rahmen einer Umfrage mit 253 Be schäftigten untersucht, ob das ganzheitliche Konzept "Total Worker Health ® (TWH)" bekannt ist und wie es in die Unternehmenskultur integriert werden könnte. Ungefähr 74 % der Befragten waren mit dem Konzept vertraut.…”
Section: Einordnung Der Ergebnisseunclassified
See 1 more Smart Citation
“…Ganzheitliche Ansätze der arbeitsmedizinischen Betreuung wer den auch international diskutiert. In einer USamerikanischen Studie (Olszewski et al 2021) wurde im Rahmen einer Umfrage mit 253 Be schäftigten untersucht, ob das ganzheitliche Konzept "Total Worker Health ® (TWH)" bekannt ist und wie es in die Unternehmenskultur integriert werden könnte. Ungefähr 74 % der Befragten waren mit dem Konzept vertraut.…”
Section: Einordnung Der Ergebnisseunclassified
“…Bei einer Literaturrecherche diverser Datenbanken mit 1287 Treffern über livivo.de (Suchbegriffe: "arbeits medizinisch" und "Vorsorge") wurden Studien in Deutschland im Zeitraum von 1995 bis 2022 berücksichtigt. Mit dem Schwerpunkt auf Organisation und Durchführung von AMV sind einige qualita tive Studien (Barth et al 2014;Grooten et al 2016;Michaelis et al 2013a,b;Preiser et al 2013;Stranzinger u. Nienhaus 2018;Stran zinger et al 2016;Stratil et al 2017a,b;Stratil et al 2018;Voelter Mahlknecht et al 2013, 2017, Querschnittuntersuchungen (Berger 2005;Hoge et al 2019;Olszewski et al 2021;Peters et al 2017;Seibt et al 2011;Winkler et al 2015), eine Kohortenstudie (Ott et al 2010) sowie ein Pilotprojekt zur sicherheitstechnischen und be triebsärztlichen Betreuung (Bell 2022;Bell et al 2021) veröffentlicht. Direkt in Bezug auf die Einflussfaktoren und die Ergebnisse eines ganzheitlichen Vorgehens in der AMV liegen auch aus diesen Studien keine Aussagen vor.…”
Section: Introductionunclassified
“…As this definition suggests, workplace health management is a holistic approach, and there is a strong similarity between workplace health management and the 'Total Worker Health' concept that has been promoted in the USA [5][6][7][8][9][10][11][12][13][14]. In recent years, this approach has further gained ground [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31]. Workplace health management can be differentiated into the following four subcategories [4]: (1) occupational health and safety measures, (2) management of return-to-work processes of employees who were on long-term sickness absence (in short 'reintegration management'), (3) workplace health promotion measures, and (4) supporting personnel development.…”
Section: Introduction 1backgroundmentioning
confidence: 99%
“…OHPs can be transformational change leaders by embracing the concept of TWH and integrating TWH programs within their organizations (Olszewski et al, 2021). There are many TWH resources available within the NIOSH TWH webpage to begin the process of TWH program implementation: resources, such as organizational assessment and evaluation tools, to assist in benchmarking an organization’s readiness, and tools to assist in making the business case on why the initiatives would be implemented.…”
mentioning
confidence: 99%
“…In 2016, the American Association of Occupational Health Nurses (AAOHN) signed on as a TWH and affiliate, and now there are more than 54 organizations as affiliate members. Olszewski et al (2021) conducted a research study with AAOHN membership. Findings of this research study indicated that most occupational health professionals (OHPs) know about TWH, but generally have not adopted the TWH concept at their worksites.…”
mentioning
confidence: 99%